Influence of different pretreatments and drying methods on the chemical compositions and bioactivities of Smilacis Glabrae Rhizoma - Juanjuan Qiao; Gengyu Lu; Gang Wu; Hui Liu; Wanli Wang; Tianmao Zhang; Guoyong Xie; Minjian Qin (BMC, 2022)
Abstract Background The processing of medicinal plant materials is one of the important factors influencing the components and biological activities of TCMs. Smilax glabra Roxb. is an herbal vine widely distributed in China, and its dried rhizome (Smilacis Glabrae Rhizoma, SGR) is often used in traditional medicines and functional foods. The processing methods of fresh cutting for SGR slices have been included in ancient Chinese herbal works, some local standards of TCMs, and the current Chinese Pharmacopoeia. Nevertheless, to date, the scientific basis for the processing of fresh medicinal materials for SGR slices has not been revealed. Methods To optimize the processing method for preparing SGR slices from the fresh rhizomes, the chemical compositions of the un-pretreated and pretreated (boiling, steaming) samples before and after drying (sun-drying, shade-drying, oven-drying), and the contents of astilbin isomers in dried SGR were analyzed by UHPLC-Q-TOF-MS/MS and UHPLC-DAD methods, respectively. Then, the antioxidant, anti-inflammatory, xanthine oxidase and α-glucosidase inhibitory activities of the prepared SGR slices were investigated by biological assays. Results A total of fifty-two compounds were identified from the un-pretreated and pretreated samples and a total of forty-nine compounds were identified from the subsequently dried samples. After pretreated by boiling and steaming, the contents of neoastilbin, neoisoastilbin, and isoastilbin in the prepared samples all increased. As a quality marker of SGR, the content of astilbin was unchanged or decreased slightly compared with that in the un-pretreated samples. During the drying process, the contents of the four astilbin stereoisomers in the un-pretreated samples increased significantly, while those in the pretreated samples had a slight increase or decrease. The effects of different processing methods were sorted according to the bioactivities of the prepared SGR. As a result, SGR slices prepared with no pretreatment followed by a sun-drying process have a higher astilbin content, better bioactivities and more energy savings, representing the optimum processing method for SGR slices. Conclusions This study reveals the scientific basis for the processing of fresh medicinal materials for SGR slices. The results provide scientific information for the quality control of SGR and its rational applications in herbal medicines and functional foods. Graphical abstract